Atomization modelling using adaptive mesh refinement modeling liquid jet atomization using adaptive mesh refinement - Sipatov, Aleksey Matveevich; Karabasov, Sergey Aleksandrovich; Gomzikov, Leonid Yulievich; Abramchuk, Taras Viktorovich; Semakov, Gleb Nikolaevich (Computational Continuum Mechanics, 2015)
Atomization of liquid jets due to air flow has a wide range of practical applications. A three-dimensional numerical analysis becomes increasingly important for designing and design development of liquid spraying systems, yet it has to be verified. The results of numerical simulations obtained using adaptive mesh refinement are presented. Two cases are considered: dispersion of a cylindrical jet in a crossflow air and liquid film destruction due to impingement of two jets. A comparison with the available experimental data has been performed. The problems under study make it possible to investigate such physical mechanisms governing atomization as the effect of airflow parameters and the instability of liquid film under mechanical impact. The influence of the quality of a computational mesh on the accuracy of the flow description is examined using the VOF (Volume of Fluid) approach. It is shown that the adaptive mesh refinement assures determination of liquid film boundaries and droplet sizes with a satisfactory accuracy even on relatively small meshes. It has been found that not only the choice of an adaption algorithm has a sufficient influence on the simulation results, but also the type of an initial mesh (regular hexahedral or irregular isotropic tetrahedral). Calculation parameters are presented at which good agreement with the experimental data has been obtained. The VOF approach combined with an adaptive mesh refinement provides high accuracy computations of liquid jet atomization processes.
Keywords: computational fluid dynamics; VOF approach; adaptive atomization; aerosol characteristics; liquid film atomization; jet-on-jet impingement; jet atomization